The Upright Project's Effectiveness in Preventing Adolescents Bullying in Schools - Nasution, Riska Amalya; Meinarisa; Nurlinawati; Falani, Ilham (Journal for Lesson and Learning Studies, 2024)
The underlying issue of this research is the high prevalence of bullying among adolescents, which adversely affects their mental health, social well-being, and academic development. This study aims to evaluate the effectiveness of the Upright Project as a preventive measure against bullying in school-aged adolescents. A quantitative approach was employed with a quasi-experimental design, specifically a quasi-experimental pre-posttest with control group, to measure changes in bullying behavior and student resilience levels before and after program implementation. The sample consisted of 113 students aged 12 to 18, identified as a vulnerable group to bullying experiences. Bullying victimization levels were assessed using a questionnaire, and data were analyzed using univariate and bivariate techniques with Wilcoxon and Mann-Whitney tests. The findings revealed that the implementation of the Upright Project significantly reduced reported cases of bullying. Additionally, there was an improvement in students' resilience in coping with adversity. Posttest analysis indicated significant differences between the intervention and control groups, with the intervention group demonstrating the program's effectiveness. This study concludes that the Upright Project is an effective intervention for reducing bullying behavior and enhancing student resilience. These findings highlight the importance of implementing similar intervention-based programs to create safer school environments that support adolescent development.